CAN OWNERSHIP STRUCTURE AND AUDIT QUALITY COLLABORATE TO REDUCE CORPORATE TAX AGGRESSIVENESS? - Mufidaturrohmah, Nur; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The escalation in instances of Corporate Tax Aggressiveness has emerged as a notable apprehension for governmental entities and stakeholders in the corporate realm. The present investigation delves into the repercussions of managerial ownership, institutional ownership, Public Accounting Firm (KAP) magnitude, and audit duration on corporate tax aggressiveness. The examination encompasses a cohort of 51 organizations operating in the real estate, property, healthcare, transportation, and industrial domains, which are publicly listed on the Indonesia Stock Exchange (IDX) spanning from 2019 to 2023. This study relies on secondary data extracted from annual financial statements and adopts a non-probability sampling technique. The outcomes of the statistical analysis manifest that both managerial and institutional ownership do not wield a substantial influence on corporate tax aggressiveness, and the size of KAP demonstrates negligible impact. Nevertheless, the audit tenure exhibits a markedly adverse effect, signifying that an elongated association with the auditor diminishes corporate tax aggressiveness. This research offers invaluable insights into the determinants of corporate tax aggressiveness in Indonesia and contributes to the body of knowledge by scrutinizing sectors that have received scant attention. Prospective research endeavors could delve into exploring additional variables that might impinge on corporate tax aggressiveness.